PEMBINAAN SIKAP DISIPLIN ANAK MELALUI PEMBIASAAN KEGIATAN SEHARI HARI DALAM PRESPEKTIF PENDIDIKAN SEPANJANG HAYAT : STUDI KUALITATIF DI PANTI ASUHAN - Sani Susanti; Michael Yudha Pratama; Dedek Fadila Tri Julianta Tarigan; Adam Elvano Tambunan; Ester Piani Telaumbanua; Lara Sungam Br Ginting; Maharani Cheche Kiranti; Nazwa Alya Fasya; Mutiara Seven Manalu; Marcella Pebrina Br Tarigan; Fanny Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the development of children’s discipline through habituation of daily activities at the Olivia Zerlinda Orphanage Foundation. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving orphanage administrators and children as participants. The data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that discipline is fostered through structured and scheduled daily activities such as group learning, religious practices, and environmental maintenance. Furthermore, the assignment of responsibilities and the role of caregivers as mentors and role models strengthen the formation of disciplined behavior. Children who consistently participate in these activities demonstrate more orderly behavior, greater adherence to rules, and better time management. Therefore, continuous and consistent habituation of daily activities is proven effective in developing discipline among children and supporting character education within the orphanage environment.